Ectopic adrenal cortical tissue presenting as gastrohepatic ligament "lymph node" diagnosed by fine‐needle aspiration: A case report. Issue 6 (17th April 2023) - Ho, Linh; Policarpio‐Nicolas, Maria Luisa C.
Abstract: Ectopic adrenal cortical tissue has been reported in several locations, most often involving the retroperitoneal fat close to the adrenal gland. The reported cases presenting adjacent or proximal to the stomach are rare and mostly diagnosed on histology. To our knowledge, the cytologic features of ectopic adrenal cortical tissue diagnosed on fine needle aspiration are not well documented in the cytology literature. We describe the cytologic features of ectopic adrenal cortex which initially presented on imaging study as an enlarged gastrohepatic ligament "lymph node" on a patient with gastric signet ring cell carcinoma. The aspirates showed small clusters and cords of uniform cells with abundant vacuolated to densely compact cytoplasm, occasionally stripped nuclei, and delicate frayed cytoplasmic membranes dispersed in a bubbly, vacuolated background. Immunohistochemical stains performed on the corresponding cell block showed these cells were positive for SF‐1 and negative for PAX 8. The corresponding biopsy showed similar findings in addition to immunoreactivity to inhibin. Because the cytologic features of ectopic adrenal cortical tissue especially on unusual sites could easily mimic malignant neoplasms, familiarity with the cytologic features in conjunction with immunohistochemical stains are key in arriving at the correct diagnosis and avoiding misdiagnosis.